Revision of the genus Siolicaris Jakobi, 1972, with redescriptions of S. sioli (Noodt, 1963) and S. jakobi (Noodt, 1963) from South America, and S. sandhya (Ranga Reddy, 2001) comb. nov. from India (Copepoda, Harpacticoida, Parastenocarididae) - Corgosinho, P.h.c.; Reddy, Y. Ranga; Arbizu, P. Martínez (Zootaxa, 2012)
Recent revision of the family Parastenocarididae has revealed the existence of different monophyletic groups within therepository genus Parastenocaris Kessler, 1913 sensu lato. Here, we redefine the genus Siolicaris Jakobi, 1972, arguingfor its monophyly. All the hitherto known Neotropical species of Siolicaris and also the Indian Siolicaris sandhya (RangaReddy, 2001) comb. nov., which are redescribed herein, share what we consider to be a unique constellation of synapo-morphies: in the female, thoracopod 3 enp is absent; in the male, thoracopod 4 enp is reduced; thoracopod 3 exp is robust,strongly incurved and with a very strong thumb, longer than apophysis; and in both sexes, thoracopod 5 is trapezoidal,with all the setigerous elements inserted on the very distal margin. In addition, the proximal position of furcal setae I–IIItogether with the extreme reduction of seta II and the reduction or complete absence of the proximal-most seta on thora-copod 5 exp are other good indications, justifying the inclusion of Siolicaris within a broader group of Neotropical Paras-tenocarididae. The genus is probably of Gondwanan origin, with its known members distributed in the northern SouthAmerica (Amazonian region) and southeastern India. Parastenocaris digitata Noodt, 1963a is treated here as a synonymof Siolicaris jakobi (Noodt, 1963a). Parastenocaris chelifer Delachaux, 1924 and Parastenocaris xyrophora Noodt & Galhano, 1969 are considered species inquirendae of the genus Siolicaris, pending their detailed redescription.